2020
DOI: 10.1186/s12889-020-09409-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of quadrivalent influenza vaccines in Brazil: a cost-effectiveness analysis using an influenza transmission model

Abstract: Background Influenza epidemics significantly weight on the Brazilian healthcare system and its society. Public health authorities have progressively expanded recommendations for vaccination against influenza, particularly to the pediatric population. However, the potential mismatch between the trivalent influenza vaccine (TIV) strains and those circulating during the season remains an issue. Quadrivalent vaccines improves vaccines effectiveness by preventing any potential mismatch on influenza … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The impact of replacing the TIV by QIV in a pediatric group has been estimated. When the dynamic epidemiological model was applied to the Brazilian context, QIV adoption would be able to avoid 406,600 symptomatic cases, 11,300 hospitalizations, and almost 400 deaths per influenza season, reinforcing the cost-effectiveness of QIV and its respective public health benefits [ 58 , 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of replacing the TIV by QIV in a pediatric group has been estimated. When the dynamic epidemiological model was applied to the Brazilian context, QIV adoption would be able to avoid 406,600 symptomatic cases, 11,300 hospitalizations, and almost 400 deaths per influenza season, reinforcing the cost-effectiveness of QIV and its respective public health benefits [ 58 , 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies from all regions of the world have demonstrated the significant economic benefits of QIV use compared with TIV [ 9 , 10 , 11 , 16 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Currently in Argentina, the National Immunization Program recommends annual receipt of TIV for individuals classified as “at risk”.…”
Section: Discussionmentioning
confidence: 99%
“…Jamotte et al estimate that the use of QIV in Brazil, Colombia, and Panama would significantly reduce the burden of seasonal influenza disease in these countries [ 8 ]. Studies from Mexico and Brazil have shown that the use of quadrivalent rather than trivalent vaccines in these countries would be cost-effective [ 9 , 10 , 11 ]. These and other data suggest that the introduction of QIV in Argentina could potentially be of benefit.…”
Section: Introductionmentioning
confidence: 99%
“…Even allowing for this variability, numerous health economic evaluations have suggested that replacing TIV with QIV is cost-effective in eligible populations (generally children ≤4 years of age, adults ≥65 years of age, other adults at high risk of influenza complications, or subgroups of these categories). The switch to QIV has been demonstrated to be cost-effective in a number of local settings around the world, as reported in a systematic review 1 and for several countries, for example Canada, 10 Italy, 11 Germany, 12 Spain, 13 Brazil, 14 China, 15 South Korea, 16 and Japan. 17 Benefits from switching from TIV to QIV have also been demonstrated in a Latin American context, for example in Brazil, Colombia, Panama, and Mexico.…”
Section: Introductionmentioning
confidence: 93%
“… 17 Benefits from switching from TIV to QIV have also been demonstrated in a Latin American context, for example in Brazil, Colombia, Panama, and Mexico. 14 , 18–20 …”
Section: Introductionmentioning
confidence: 99%